Multi-stage hydrogel rockets with stage dropping-off by thermal/light stimulation. Issue 35 (24th August 2018) - Liang, Yuling; Xu, Yibin; Ye, Wei; Yao, Dahua; Chen, Yunhua; Wang, Chaoyang
Abstract : A multi-stage hydrogel rocket with precise control of the step-by-step detachment of the hydrogel stage and tunable cargo release ability was fabricated. Abstract : The emerging micromotors have shown great potential as delivery vehicles due to their promising transport capacity and ability to dynamically respond to the environment. We report here a multi-stage hydrogel rocket with precise control of the step-by-step detachment of the hydrogel stage and tunable cargo release ability. The hydrogel rocket, constructed from driving hydrogel blocks alternating with sacrificial hydrogel blocks, could propel itself fast driven by the Marangoni effect and drops off self-propelled small rockets by thermal/light stimulation. Furthermore, the tunable release of the payload in the hydrogel rocket was demonstrated. This multi-stage hydrogel rocket may provide new insight into the design of micromotors with on-demand cargo transport and delivery capabilities.